Experimental feeding of Sergentomyia minuta on reptiles and mammals: comparison with Phlebotomus papatasi - Lucie Ticha; Vera Volfova; Jairo Alfonso Mendoza-Roldan; Marcos Antonio Bezerra-Santos; Carla Maia; Jovana Sadlova; Domenico Otranto; Petr Volf (Parasites & Vectors, 2023)
Abstract Background Sergentomyia minuta (Diptera: Phlebotominae) is an abundant sand fly species in the Mediterranean basin and a proven vector of reptile parasite Leishmania (Sauroleishmania) tarentolae. Although it feeds preferentially on reptiles, blood meal analyses and detection of Leishmania (Leishmania) infantum DNA in wild-caught S. minuta suggest that occasional feeding may occur on mammals, including humans. Therefore, it is currently suspected as a potential vector of human pathogens. Methods A recently established S. minuta colony was allowed to feed on three reptile species (i.e. lizard Podarcis siculus and geckos Tarentola mauritanica and Hemidactylus turcicus) and three mammal species (i.e. mouse, rabbit and human). Sand fly mortality and fecundity were studied in blood-fed females, and the results were compared with Phlebotomus papatasi, vector of Leishmania (L.) major. Blood meal volumes were measured by haemoglobinometry. Results Sergentomyia minuta fed readily on three reptile species tested, neglected the mouse and the rabbit but took a blood meal on human. However, the percentage of females engorged on human volunteer was low in cage (3%) and feeding on human blood resulted in extended defecation times, higher post-feeding mortality and lower fecundity. The average volumes of blood ingested by females fed on human and gecko were 0.97 µl and 1.02 µl, respectively. Phlebotomus papatasi females readily fed on mouse, rabbit and human volunteer; a lower percentage of females (23%) took blood meal on the T. mauritanica gecko; reptilian blood increased mortality post-feeding but did not affect P. papatasi fecundity. Conclusions Anthropophilic behaviour of S. minuta was experimentally demonstrated; although sand fly females prefer reptiles as hosts, they were attracted to the human volunteer and took a relatively high volume of blood. Their feeding times were longer than in sand fly species regularly feeding on mammals and their physiological parameters suggest that S. minuta is not adapted well for digestion of mammalian blood. Nevertheless, the ability to bite humans highlights the necessity of further studies on S. minuta vector competence to elucidate its potential role in circulation of Leishmania and phleboviruses pathogenic to humans. Graphical abstract